AI-Enhanced Strategies for COVID-19 Vaccination and Booster Prioritization: A Comprehensive Framework - Sara AlShaya; Aji Gopakumar; Rahul Raghupathy; Badshah Mukherjee; Bachir Abou Elias; Sheik Jamal Mohideen; Vibhor Mathur; Sudheer Kurakula (National Journal of Community Medicine)
Background: Distributing vaccines efficiently during the COVID-19 pandemic presented significant logistical challenges. To address the need for identifying populations at risk of breakthrough infections and those requiring booster shots, Emirates Health Services (EHS) developed a framework utilizing AI-driven digital solutions. Objective: To develop a machine learning (ML) model to identify individuals at risk of breakthrough infections and in need of booster doses, aiming to prioritize booster administration and reduce repeated infections among fully vaccinated individuals in the Northern Emirates of the UAE.